2017
DOI: 10.1111/jam.13491
|View full text |Cite
|
Sign up to set email alerts
|

A nano particle vector comprised of poly lactic-co-glycolic acid and monophosphoryl lipid A and recombinant Mycobacterium avium subsp paratuberculosis peptides stimulate a pro-immune profile in bovine macrophages

Abstract: These results will assist on more in depth studies on PLGA NP delivery systems that may lead to the development of a peptide-based vaccine for cattle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
3
0
2
Order By: Relevance
“…An early attempt to develop a nano particle-based vaccine incorporating eMMP was not successful (29). Initial studies demonstrated eMMP could be encapsulated in a nano particle lipid carrier and elicit a recall response.…”
Section: Discussionmentioning
confidence: 99%
“…An early attempt to develop a nano particle-based vaccine incorporating eMMP was not successful (29). Initial studies demonstrated eMMP could be encapsulated in a nano particle lipid carrier and elicit a recall response.…”
Section: Discussionmentioning
confidence: 99%
“…Although MPL lacks undesirable effects of LPS [ 25 ], it can still induce immune cell activation [ 40 , 41 ]. In the current study, minocycline pretreatment was found to suppress acute MPL injection-induced neuroinflammatory responses in the brain and simultaneously abrogate the preventive effect of MPL pre-injection on CSDS-induced anxiety-like behaviors in mice.…”
Section: Discussionmentioning
confidence: 99%
“…For example, poly-IC (a synthetic analog of double-stranded RNA), which is recognized through TLR3 and the cytosolic receptor MDA5 (melanoma differentiation-associated gene 5), stimulates Th1 cell immunity, including the generation of cytotoxic CD8 T lymphocytes in mice [157]. A low-toxicity derivative of LPS, monophosphoryl lipid A (MPLA), stimulates TLR4 by the TRIF pathway and biases the response towards Th1 immunity in mice and humans [165], and possibly in cattle [166]. The action of MPLA, which is used in the mastitis vaccine UBAC ® (Hipra S.A.), deserves to be delineated in detail in the bovine species.…”
Section: Improve Knowledge Of Adjuvants For Ruminants To Guide the Im...mentioning
confidence: 99%